2019
DOI: 10.1149/2.0241905jss
|View full text |Cite
|
Sign up to set email alerts
|

Editors' Choice—In Situ Electrochemical Evaluation of Post-CMP Cleaning Reactions for Cobalt and Copper Films under Brushing Conditions

Abstract: The sub-10 nm technology node has introduced significant chemical complexities in the associated processing steps of chemical mechanical planarization (CMP), and this has correspondingly convoluted the post-CMP cleaning (PCMPC) protocols. Focusing on selected cleaning chemistries, the present work demonstrates an in-situ tribo-electrochemical approach to developing fundamental knowledge of the PCMPC mechanisms for such systems. As model samples, the experiments use cobalt and copper thin films, deposited on wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…7 The strategy of maintaining mutually similar chemical environment between CMP and PCMPC processes has been used by other authors, 26 and this approach has been helpful for developing analytical PCMPC characterization protocols. 5 In the PCMPC setting, surface coverages of CMP residues should be substantially lower than those of the same species being generated in a CMP solution as primary materials for planarization. Therefore, while using mutually similar chemical routes to CMP and PCMPC, the overall surface activity of the PCMPC solution should be maintained at a substantially lower level than that of the CMP solution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…7 The strategy of maintaining mutually similar chemical environment between CMP and PCMPC processes has been used by other authors, 26 and this approach has been helpful for developing analytical PCMPC characterization protocols. 5 In the PCMPC setting, surface coverages of CMP residues should be substantially lower than those of the same species being generated in a CMP solution as primary materials for planarization. Therefore, while using mutually similar chemical routes to CMP and PCMPC, the overall surface activity of the PCMPC solution should be maintained at a substantially lower level than that of the CMP solution.…”
Section: Resultsmentioning
confidence: 99%
“…A stainless-steel counter electrode (CE) and a saturated calomel (SCE) reference electrode (RE, separated from the main solution with a salt bridge), completed the three-electrode setup. The detailed components of this cell have been previously discussed, 5 and for ease of reference, is schematically depicted here in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This occurs mainly due to the chemisorption and physisorption of the TAZ molecules on the metal surfaces. 186 Johnson et al 187 reported that oxalate ions of oxalic acid accompanied by brush scrubbing effectively removed the residues such as Co(OH) 2 ,Co(BTA) 2 ,Cu-oxides and Cu-BTA from Co and Cu obtained after polishing in an abrasives free CMP slurry. Surface alterations were not observed post cleaning and a removal efficiency of 85% -89% was obtained for both the metals.…”
Section: Application-based Post-cmp Cleaningmentioning
confidence: 99%